2018
DOI: 10.1177/0300985818758467
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Lesions of the Endometrium of 50 Four-Toed Hedgehogs (Atelerix albiventris)

Abstract: Uteri from 50 four-toed hedgehogs ( Atelerix albiventris) with clinical signs of uterine disease were histopathologically examined. Sixteen animals (32%) were diagnosed with endometrial hyperplasia, 7 animals (14%) were diagnosed with endometrial polyp, and 27 animals (54%) were diagnosed with endometrial neoplasia. The mean ages of the animals with endometrial hyperplasia, polyp, and neoplasia were 28.7 months, 29.4 months, and 25.2 months, respectively. The neoplasms were classified into 7 endometrial mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
1
10
0
1
Order By: Relevance
“…The presence of ascites has been reported in hedgehogs with proliferative uterine lesions [3] and granulosa cell tumors [7]. In this study, ascites was identified in 50% patients.…”
Section: The Medical Records Of Eight Hedgehogs Admitted To Miwa Exotsupporting
confidence: 54%
“…The presence of ascites has been reported in hedgehogs with proliferative uterine lesions [3] and granulosa cell tumors [7]. In this study, ascites was identified in 50% patients.…”
Section: The Medical Records Of Eight Hedgehogs Admitted To Miwa Exotsupporting
confidence: 54%
“… ). These uterine polyps were classified histologically into 3 categories, based on the World Health Organization (WHO) classification for humans [ 2 , 13 ], and included one non-neoplastic and 2 neoplastic lesions.…”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of neoplasms are commonly present in captive hedgehogs, especially in the APH (Raymond and Gamer 2001;Gadrhouse and Eshar 2015;Tsai et al 2016;Chambers et al 2018). The average lifespan of the APH is 3-5 years and the average age for the appearance of neoplasms is 3.5 years (Heatley 2009;Matute et al 2014).…”
Section: Discussionmentioning
confidence: 99%